ANALISIS DEFLEKSI BENDA KERJA DITINJAU DARI KEDALAMAN POTONG PADA PROSES BUBUT - Yeremia Sianturi; Stenly Tangkuman; Irvan Rondonuwu (JURNAL POROS TEKNIK MESIN UNSRAT, 2020)
The purpose of this research is to obtain relations of workpiece’s deflection toward cutting force related to gripping distance, and to analize deflection towards parameters of the depth cutting and cutting rotation velocity at 300 rpm and 1600 rpm. The first result, is the deflection of workpiece is getting larger by the depth of cutting is increases. The second result, is the difference of deflection towards cutting rotation velocity variations. Number of workpiece’s deflection, showed small reduction at 300 rpm towards 1600 rpm. However, deflections numbers remain constant showed by the statistics data, because of the small variation. This research showed that, at the low cutting velocity the workpiece’s deflection is larger compare to high cutting velocity. Refer to deflection number, the recommended cutting velocity is 1600 rpm.Keywords: Depth of cutting, Deflection of workpiece, The lathe